Wilhelm Lehmbruck Museum : Zentrum Internationaler Skulptur Duisburg. - Wilhelm-Lehmbruck-Museum, Duisburg; Brockhaus, Christoph; Dinkla, Söke; Heidt Heller, Renate; Leinz, Gottlieb; Lepper, Katharina; Schlenke, Hubertus (München : Prestel Verlag, 2000)
Archipenko, Alexander ; Arp, Hans (Jean) ; Baranov-Rossiné, Vladimir ; Barlach, Ernst ; Baumeister, Willi ; Beckmann, Max ; Belling, Rudolf ; Beuys, Joseph ; Bill, Max ; Boltanski, Christian ; Brancusi, Constantin ; Brauner, Victor ; Breloh, Heinz ; Buchholz, Erich ; Calder, Alexander ; Campendonk, Heinrich ; César ; Chadwick, Lynn ; Chillida, Eduardo ; Christo ; Dali, Salvador ; Derain, André ; Dexel, Walter ; Disler, Martin ; Ernst, Max ; Feininger, Lyonel ; Riverhead (New York) ; Fontana, Lucio ; Freundlich, Otto ; Fritsch, Lutz ; Gabo, Naum ; Gargallo, Pablo ; Genzken, Isa ; Giacometti, Alberto ; González, Julio ; Hanson, Duane ; Heckel, Erich ; Heerich, Erwin ; Hepworth, Barbara ; Herzog, Oswald ; Hoehme, Gerhard ; Hunt, Bryan ; Ioganson, Karl V. ; Jawlensky, Alexej von ; Jetelova, Magdalena ; Judd, Donald ; Kadishman, Menashe ; Kaprow, Allan ; Karavan, Dani ; Kaufmann, Andreas M. ; Kirchner, Ernst Ludwig ; Kokoschka, Oskar ; Kollwitz, Kathe ; Kounellis, Jannis ; Kricke, Norbert ; Lang, Nikolaus ; Lardera, Berto ; Laurens, Henri ; Lebedev, Vladimir ; Lechner, Alf ; Lehmbruck, Wilhelm von ; LeWitt, Sol ; Lipchitz, Jacques ; Long, Richard ; Loth, Wilhelm ; Macke, August ; Magritte, René ; Man Ray ; Marc, Franz ; Marcks, Gerhard ; Marini, Marino ; Mataré, Ewald ; Merz, Mario ; Minne, George ; Moholy-Nagy, Laszlo ; Molzahn, Johannes ; Moore, Henry ; Muche, Georg ; Mueller, Otto ; Nay, Ernst Wilhelm ; Nestler, Wolfgang ; Nevelson, Louise ; Noguchi, Isamu ; Nolde, Emil ; Oppenheim, Meret ; Paik, Nam June ; Pan, Marta ; Paolozzi, Eduardo ; Pechstein, Max ; Penck, A.R. ; Péri, László ; Pevsner, Antoine ; Picasso, Pablo ; Pomodore, Arnaldo ; Puni, Ivan ; Rabinowitch, David ; Radermacher, Norbert ; Richier, Germaine ; Richter, Gerhard ; Rickey, George ; etc.
Duits
boek